LUMEN D8.3 Update plan for communication and dissemination - Arasteh-Roodsary, Sona; Foumany, Léa; Delmazo, Caroline; Mystakopoulos, Fotis; Homo, Julien (Zenodo (CERN European Organization for Nuclear Research), 2026)
This document is an update to LUMEN Deliverable (D) 8.2 “Communication and Dissemination Plan”. D8.3 gives an overview of the current status of communication and dissemination activities in its introduction in chapter 2. Chapter 3 explains why and how the priorities of communication and dissemination activities have been reshifted to community building and the promotion of the project’s Key Exploitable Results (KERs). Notably, chapter 3 includes a communication profile for each KER and concludes by presenting the value proposition of each KER per individual stakeholder category. Chapter 4 explains the engagement strategy of the project in more detail, with individual plans for a webinar series, a dedicated White-Label Platform event campaign and engagement measures specifically tailored to the four scientific domains of the project: Molecular Dynamics, Earth System Science, Mathematics and Social Sciences and Humanities. Lastly, chapter 5 summarises the most important aspects of the deliverable in a conclusion. This deliverable is currently under review by the EC.